Pendampingan Pemanfaatan e-Komik sebagai Media Pembelajaran Teks Negosiasi Siswa Kelas X SMA Sunan Drajat Sugio: Assistance in the Use of e-Comics as a Learning Media for Negotiation Texts for Class X Students of Sunan Drajat Sugio High School - Evy Dwi Cahyati Ningsih; Ninis Meilina Rahmawati; Sutardi Sutardi; Badi' Zamani Rohman (Pengabdian Pendidikan Indonesia, 2026)
Learning negotiation texts in grade X at Sunan Drajat High School shows that student engagement in analyzing the structure, linguistic elements, and negotiation strategies still needs improvement. Students tend to understand the material only partially because the learning process focuses more on conceptual explanations than on analyzing concrete examples from their lives. This condition serves as the basis for implementing community service activities through e-comics media as an innovative learning tool that combines visual and narrative elements to help concretize the concept of negotiation texts. This community service activity was carried out on February 2, 2026, as part of a series of learning materials on negotiation texts. The e-comics are presented in a digital format accessible on students' mobile phones, thus facilitating flexible, independent use. The activity stages begin with an introduction to e-comics and their association with the basic concepts of negotiation texts, followed by reading, observing, and analyzing the comics' content in groups or individually. Students are directed to identify the objectives of the negotiation, the parties involved, the text structure, linguistic elements, and negotiation strategies used in the dialogue presented. The results of the activity show an increase in students' active participation in discussions and their ability to identify the components of negotiation texts more systematically and critically. Furthermore, learning interactions become more focused because all students are addressing the same topic. Overall, the use of e-comics has proven to create more participatory, contextual, engaging, and effective learning experiences that enhance students' understanding of negotiation texts.